Accumulation and age-related elevation of amyloid-β within basal forebrain cholinergic neurons in the rhesus monkey. (9th July 2015) - Norvin, D.; Kim, G.; Baker-Nigh, A.; Geula, C.
Highlights: Cholinergic neurons of basal forebrain accumulate amyloid-β peptide in young and old rhesus monkeys. Quantitatively, amyloid-β40 in cholinergic neurons displays an age-related increase in rhesus monkeys. Negligible amyloid-β is apparent in cortical neurons, pointing to specificity of accumulation in cholinergic neurons. Abstract: Basal forebrain cholinergic neurons (BFCN) are selectively vulnerable to damage and loss in a number of neurodegenerative disorders that afflict the elderly, particularly Alzheimer's disease. The reasons for this selective vulnerability remain poorly understood. Given that intraneuronal accumulation of the amyloid-β peptide (Aβ) has been shown to exert deleterious effects on neurons, we tested potential accumulation of Aβ within BFCN in rhesus monkeys, which like the human display age-related accumulation of this peptide in plaques. The non-isoform-specific Aβ antibodies 1282 and 6E10 and the specific antibodies to 1–40 amino acid isoform of Aβ (Aβ1–40 ) and 1–42 amino acid isoform of Aβ (Aβ1–42 ) species were used in immunohistochemical experiments of basal forebrain in young and aged rhesus monkeys. All four antibodies visualized cortical plaques in the same sections in which BFCN were examined, in aged but not in young animals. The basal forebrain region within which the BFCN are localized was virtually free of plaques. Appreciable Aβ immunoreactivity was present within the nucleus basalis of Meynert–cholinergic cell group 4 (nbM–Ch4), the major component of BFCN, with all antibodies used. Quantitation of optical density indicated significant age-related increases in immunoreactivity in nbM–Ch4 neurons with the Aβ1–40 ( p < 0.002) and 1282 ( p < 0.03) antibodies. Immunoreactivity for 6E10 displayed a small, non-significant age-related increase in nbM–Ch4 neurons ( p > 0.05). No age-related changes were detected in Aβ1–42 immunoreactivity in these neurons. Unlike the BFCN, cortical neurons within the same sections were virtually devoid of Aβ immunoreactivity, particularly with isoform-specific antibodies. Both smooth and granular intraneuronal Aβ immunoreactivity, reminiscent of endosomal/lysosomal packaged peptide, were observed within nbM–Ch4 neurons. In some nbM–Ch4 neurons, 1282 immunoreactivity had the appearance of large peptide aggregates. Significant accumulation and age-related increase of Aβ in BFCN is likely to interfere with the normal functioning of these neurons. It remains to be determined if similar accumulation of Aβ occurs in human BFCN.